2022
DOI: 10.3390/healthcare10010156
|View full text |Cite
|
Sign up to set email alerts
|

Super-Spreaders or Victims of Circumstance? Childhood in Canadian Media Reporting of the COVID-19 Pandemic: A Critical Content Analysis

Abstract: This qualitative research study, a critical content analysis, explores Canadian media reporting of childhood in Canada during the COVID-19 global pandemic. Popular media plays an important role in representing and perpetuating the dominant social discourse in highly literate societies. In Canadian media, the effects of the pandemic on children and adolescents’ health and wellbeing are overshadowed by discussions of the potential risk they pose to adults. The results of this empirical research highlight how you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…I apply thematic analysis (Braun & Clarke, 2006, 2012; Ciotti et al, 2022; Glaw et al, 2017; Vaismoradi et al, 2013) as a primary method to analyze multiple data sources (i.e., photos, social media posts, medical documents and records, medical expenses, and email) in this autoethnography. I used photo elicitation and autophotography which are commonly used techniques in ethnographic research (Glaw et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…I apply thematic analysis (Braun & Clarke, 2006, 2012; Ciotti et al, 2022; Glaw et al, 2017; Vaismoradi et al, 2013) as a primary method to analyze multiple data sources (i.e., photos, social media posts, medical documents and records, medical expenses, and email) in this autoethnography. I used photo elicitation and autophotography which are commonly used techniques in ethnographic research (Glaw et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…I utilize reflexivity (Doucet, 2018a, 2018b; Etherington, 2017; Finefter-Rosenbluh, 2017; Fook, 1999; Hemmings, 2012) and reflective journaling (Sealy, 2012) as methods in this autoethnography. I use memory as data, by writing a personal narrative (Ellis & Bochner, 2000), and systematically analyze multiple relevant data sources (i.e., photos, social media posts, medical documents and records, medical expenses, and email) using thematic analysis (Braun & Clarke, 2006, 2012; Ciotti et al, 2022; Glaw et al, 2017; Vaismoradi et al, 2013). These additional sources of data were included as a method of checking my memories and addressing potential concerns regarding academic value in my work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though evidence reported that children may not be potential COVID-19 spreaders [ 2 , 3 ], it may have been hard to make a decision about the school reopening because of the effects of the school reopening on disease spread [ 4 ], which depended on the prevalence of COVID-19 infection in each area [ 5 , 6 ], as well as its effects on stakeholders, including teachers, parents, and students [ 7 ]. Focusing on students during the pandemic, students were either a “risk to others” or “people at risk” [ 8 ]. As a “risk to others”, adolescents, unlike young children, had a more independent lifestyle and social life, including outside activities such as hanging out with peers, which may have resulted in a higher secondary-attack rate [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless in practice the corona-discourse showed them being mere objects of public measures and discussions (cf. as an example from the Canadian discourseCiotti et al, 2022; for Germany seeVoigts, 2021).…”
mentioning
confidence: 99%